Disease evolution in systemic juvenile idiopathic arthritis: an international, observational cohort study through JIRcohort - M. Wallimann; K. Bouayed; E. Cannizzaro; D. Kaiser; A. Belot; E. Merlin; S. Poignant; C. Wouters; F. Hofer; T. Saurenmann; A. Koryllou; R. Carlomagno; et al. (BMC, 2023)
Abstract Background Systemic juvenile idiopathic arthritis (systemic JIA) is a severe disease with both systemic and joint inflammation. This study aims to identify predictors of disease evolution within the systemic JIA population enrolled in the Juvenile Inflammatory Rheumatism cohort (JIRcohort). Methods Observational patient cohort study with 201 recruited children from 4 countries (3 European, 1 North Africa) from 2005 until 2019, using retrospectively (2005-2015) and prospectively (2015-2019) routine care collected data. Results Sixty-five patients with complete follow-up data for 24 months after first diagnosis were classified as monophasic (n = 23), polyphasic (n = 6) or persistent group (n = 36) corresponding to their evolution (unique flare, recurrent flares, or persistent disease activity respectively). The patients of the persistent group were more likely to have an earlier disease onset, before the age of 6 (OR 2.57, 95%-CI 0.70-9.46), persistence of arthritis at 12-months post-diagnosis (OR 4.45, 95%-CI 0.58-34.20) and higher use of synthetic DMARD (sDMARD, OR 5.28, 95%-CI 1.39-20.01). Other variables like global assessment by physician and by patient and C Reactive Protein levels at 12-months post-diagnosis were assessed but without any predictive value after adjusting for confounding factors. Conclusions Our results suggest that the earlier disease onset, the persistence of arthritis throughout the first year of disease evolution and the need of sDMARD might predict a persistent disease course.